English language Teaching and Learning through Language Laboratory in Technical Institutes - Tiwari, Mrs. Sarika Srivastava; Batra, Dr J.C (IJRDO- Journal of Educational Research, 2016)
The ability to communicate effectively has become the prerequisite for anyone who ventures into anew profession; the need for developing communication skills is a much-felt phenomenon today.Both governmental and private institutions are focusing their attention on students developing theircommunicative skills. As technology has entered into every aspect of human life, it has extended itsadvanced products into the field of language learning also;The main objective of the present article is to highlight the importance of language lab in learningcommunication skills by using advance techniques in learning process. Language learning is not thesame as learning any other subject; it is not confined up to spoken English only. The four skills oflistening, speaking, reading and writing must have to be practiced and learned well. In whichlanguage lab can play an important role. As it is a technological aid for learning, it has a number ofadvanced facilities that can help students to learn a language with proficiency to communicate. Thisarticle focuses on Concept of language lab, types of laboratory, and how learning through languagelab could be easy and interesting,